"Having a non-normative body for me is about survival": Androgynous body ideal among trans and nonbinary individuals. (December 2021) - Galupo, M. Paz; Cusack, Claire E.; Morris, Ezra R.
Highlights: For trans and nonbinary (TNB) individuals androgyny served several functions. TNB conceptualized androgynous body ideals as affirming to their gender identity. Actions to achieve androgyny targeted gender expression, body shape, and sex traits. Clinical implications contribute to trans resilience models of interventions. Abstract: The present study focused on trans and nonbinary (TNB) individuals who have an androgynous or non-stereotypical body ideal, with attention to how their body ideal is conceptualized and maintained. Data were collected online from 76 TNB individuals. Based on responses to two open-ended prompts, a two-tiered analysis was conducted. First, thematic analysis was used to develop four central themes describing the way TNB individuals conceptualized their androgynous body ideal: 1) Attaining Neutrality and De-Categorizing Gender; 2) Disaggregating Gender Expression; 3) Managing Gender Dysphoria; and 4) Achieving Authenticity. Second, content analysis was used to document 12 behaviors engaged in or actions taken for the purpose of approaching or maintaining an androgynous or non-stereotypical body ideal. These were grouped into 3 main categories: gender expression (clothes, hair, make-up, body modifications), body shape (weight, muscularity, eating/diet), and sex characteristics (hormone therapy, body hair, vocal, chest, genitals). Results of the present study expand the current body ideal literature by including TNB narratives and by focusing specifically on the ways an androgynous body ideal is conceptualized and maintained. Research and clinical implications are discussed.